The Role of Innate Immunity in COVID-19 - Silva de Sordi, Luiz Henrique (2020)
The immune system plays an essential role in the COVID-19 pandemic, as it is involved in the pathogenesis and worsening of the disease. The purpose of this review is to address aspects of innate immunity in COVID-19, especially the role of neutrophils. The innate immune system corresponds to the organism's first defense, but a balance must be effective against the invader without harming the host excessively. An immune imbalance is related to more severe conditions and aberrant neutrophil activation, with lymphopenia and neutrophilia being predictors of a worse prognosis in patients with COVID-19. Neutrophilia is speculated to be an important source for the excessive formation of NET (Neutrophil Extracellular Traps), leading to increased inflammatory response and unfavorable evolution of the disease. NETs are also associated with the cytokine storm, another mechanism related to COVID-19's gravity. Therefore, strategies involving immunomodulation may have an essential role in controlling the disease.